Two Cases of Strictures after Percutaneous CT-Guided Radiofrequency Ablation for Renal Cell Carcinoma. (13th January 2020) - Heißler, Ortwin; Seklehner, Stephan; Fingernagel, Maximilian; Engelhardt, Paul F.; Riedl, Claus
Abstract : Percutaneous radiofrequency ablation is a safe and effective minimally invasive treatment option in selected patients with T1a tumors of the kidney with a low complication rate. We describe two cases that developed the rare but severe complication of thermal injury-induced strictures of the upper urinary tract and its consecutive management.